Effect of a Diet Enriched with Fresh Coconut Saturated Fats on Plasma Lipids and Erythrocyte Fatty Acid Composition in Normal Adults. (4th July 2017) - Nagashree, Rokkam Shankar; Manjunath, N. K.; Indu, M.; Ramesh, M.; Venugopal, V.; Sreedhar, P.; Pavithra, N.; Nagendra, Hongasandra R.
ABSTRACT: Objective : The objective of this study was to compare the effects of increased saturated fatty acid (SFA) (provided by fresh coconut) versus monounsaturated fatty acid (MUFA) intake (provided by a combination of groundnuts and groundnut oil) on plasma lipids and erythrocyte fatty acid (EFA) composition in healthy adults. Material and Methods : Fifty-eight healthy volunteers, randomized into 2 groups, were provided standardized diet along with 100 g fresh coconut or groundnuts and groundnut oil combination for 90 days in a Yoga University. Fasting blood samples were collected before and after the intervention period for the measurement of plasma lipids and EFA profile. Results : Coconut diet increased low-density lipoprotein (LDL) and high-density lipoprotein (HDL) levels significantly. In contrast, the groundnut diet decreased total cholesterol (TC), mainly due to a decrease in HDL levels. There were no differences in the major SFA of erythrocytes in either group. However, coconut consumption resulted in an increase in C14:0 and C24:0 along with a decrease in levels of C18:1 n9 (oleic acid). There was a significant increase in levels of C20:3 n6 (dihomo-gamma linolenic acid, DGLA). Conclusions : Consumption of SFA-rich coconut for 3 months had no significant deleterious effect on erythrocytes or lipid-related factors compared to groundnut consumption. On the contrary, there was an increase in the anti-atherogenic HDL levels and anti-inflammatory precursor DGLA in erythrocyte lipids. This suggests that coconut consumption may not have any deleterious effects on cardiovascular risk in normal subjects.